The limits of market-based reforms in the NHS: the case of alternative providers in primary care - Coleman, Anna (BioMed Central, 2013)
BACKGROUND: Historically, primary medical care in the UK has been delivered by general practitioners who are independent contractors, operating under a contract, which until 2004 was subject to little performance management. In keeping with the wider political impetus to introduce markets and competition into the NHS, reforms were introduced to allow new providers to bid for contracts to provide primary care services in England. These contracts known as ‘Alternative Provider Medical Services’, were encouraged by two centrally-driven rounds of procurement (2007/8 and 2008/9). This research investigated the commissioning and operation of such Alternative Providers of Primary Care (APPCs). METHODS: Two qualitative case studies were undertaken in purposively sampled English Primary Care Trusts (PCTs) and their associated APPCs over 14 months (2009-10). We observed 65 hours of meetings, conducted 23 interviews with PCT and practice staff, and gathered relevant associated documentation. RESULTS AND CONCLUSIONS: We found that the procurement and contracting process was costly and time-consuming. Extensive local consultation was undertaken, and there was considerable opposition in some areas. Many APPCs struggled to build up their patient list sizes, whilst over-performing on walk-in contracts. Contracting for APPCs was ‘transactional’, in marked contrast to the ‘relational’ contracting usually found in the NHS, with APPCs subject to tight performance management. These complicated and costly processes contrast to those experienced by traditionally owned GP partnerships. However, managers reported that the perception of competition had led existing practices to improve their services. The Coalition Government elected in 2010 is committed to ‘Any Qualified Provider’ of secondary care, and some commentators argue that this should also be applied to primary care. Our research suggests that, if this is to happen, a debate is needed about the operation of a market in primary care provision, including the trade-offs between transparent processes, fair procurement, performance assurance and cost.